(untitled) (Progressive Agriculture, 2013)
The BLRI Cattle Breed 1(BCB-1) is a native cattle breed developed by Bangladesh Livestock Research Institute (BLRI) through selective breeding among indigenous cattle of Bangladesh. Data asserted from record sheets of 529 animals maintained during 1992 to 2006 were analyzed to evaluate the reproductive efficiency of BCB-1 cattle in different generations, seasons and parities. The highest percent of animals showed heat during summer season (36.88%) followed by rainy (35.73%) and winter season (27.39%). The highest percent of calving was recorded in summer (43.1%) followed by rainy (31%) and winter (26%). Sex ratio of male: female calves born according to season was the highest in summer (106.31:100) intermediate in rainy (106.06: 100) and lowest in winter (105.00:100). Age at first heat (AFH), age at first calving (AFC), calving interval (CI), service per conception (SPC), gestation length (GL) and post partum heat period (PPHP) of BCB-1 cows were 843.65±17.77, 1225.24±258.92, 451.65±6.51, 1.50±0.83, 283.31±11.50, and 105.51±3.95 days, respectively. AFS and PPHP varied with generation (p<0.01) and that of SPC and PPHP with parity of dams (p<0.05). However, AFC, GL and CI of BCB-1 females did not vary with parity, generation or season of birth. It was concluded that the overall reproductive performances of BCB-1 cattle are within the range of other indigenous cattle of Bangladesh and the at such results of reproductive characteristics may be used for planning cattle breeding strategy of the country. DOI: http://dx.doi.org/10.3329/pa.v19i2.16948 Progress. Agric. 19(2): 85 - 92, 2008